Efektifitas Peran AUSAID dalam Pelestarian Hutan Akibat Perdagangan Kuota Karbon (CO2) Antara Sumatera Barat dengan Australia Tahun 2008-2013 - Harsiwi, Resti Dwi (Global and Policy Journal of International Relations, 2016)
ABSTRACTThe quota carbon trading (CO2), by the West Sumatera and Australia under the Kyoto Protocol and the REDD, brought both positive impacts and also negative impacts. The quota carbon trading (CO2) is considered as the solution in addressing global warming and climate change issues. Unfortunately, the other side of the quota carbon trading (CO2) takes forms in the deforestation and forest degradation. In this case, AusAID acts as the mediator in solving the problems that arises between the two sides. With the AusAID taking role as mediator, it is expected that the related parties can work together for a common purpose. In regards to that matter, the AusAID works through the use of diplomacy, communication and influence, which resulted in the effective work of AusAID. In achieving their goal, there is an important role of the DSF (Decentralization Support Facility) as facilitator and inspector related mechanisms must be fulfilled by Australia, AusAID, and West Sumatera.Keywords: Kyoto Protocol, REDD, quota carbon trading (CO2), AusAID, and DSF.DOI : https://doi.org/10.33005/jgp.v4i01.1926